Impact of high-density managed aquifer recharge implementation on groundwater storage, food production and resilience: a case from Gujarat, India - Alam, Mohammad Faiz; Pavelic, Paul; Villholth, Karen G.; Sikka, Alok; Pande, S. (Elsevier, 2022)
Study region: The study region is the Kamadhiya catchment (1150 km2 ), located in the Saurashtra region of the western state of Gujarat, India. The region has seen intensive development of check dams (CDs) for groundwater recharge with an estimated 27,000 CDs constructed up until 2018. Study focus: The impact of CDs on groundwater storage, food production and resilience are assessed for Kamadhiya catchment by estimating and comparing changes, across periods of low and high CD development, in potential recharge from CDs, rainfall trends, and irrigation demand. The analysis is carried out for the period from 1983 to 2015. New hydrological insights for the region: Groundwater storage gains observed following CD development can partly be attributed to an increase in high rainfall years after several drought years. Groundwater demand for irrigation has increased substantially, outweighing increase in groundwater recharge from CDs. This deficit in supply relative to demand is greatest in dry years, and when considered together with the low inter-annual carry-over storage of the region’s hardrock aquifers, means that CDs capacity to enhance groundwater storage and mitigate the negative impacts of drought remains limited. Findings suggest that a standalone focus on MAR, unless complemented by greater emphasis on management of water demand and groundwater resources more broadly, may not be sufficient to achieve the long-term goals of sustainable groundwater and concurrently expanding agricultural crop production.